Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.joi.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

DataCite as a novel bibliometric source: Coverage, strengths and limitations

Abstract: This paper explores the characteristics of DataCite to determine its possibilities and potential as a new bibliometric data source to analyze the scholarly production of open data. Open science and the increasing data sharing requirements from governments, funding bodies, institutions and scientific journals has led to a pressing demand for the development of data metrics. As a very first step towards reliable data metrics, we need to better comprehend the limitations and caveats of the information provided by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…DataCite is a content registration service, and its Event Data API provides citation indicators for research outputs that link to DataCite records (DataCite Event Data, n.d.). DataCite has handled over 6 million DOI registrations to date, of which 42% were specifically for datasets (Robinson-Garcia et al, 2017). A sizable portion of DataCite-registered content comes from only a handful of repositories, and due to inconsistency in metadata, it is unclear whether there is disciplinary bias within the content registered via DataCite (Robinson-Garcia et al, 2017).…”
Section: Citation-based Indicatorsmentioning
confidence: 99%
“…DataCite is a content registration service, and its Event Data API provides citation indicators for research outputs that link to DataCite records (DataCite Event Data, n.d.). DataCite has handled over 6 million DOI registrations to date, of which 42% were specifically for datasets (Robinson-Garcia et al, 2017). A sizable portion of DataCite-registered content comes from only a handful of repositories, and due to inconsistency in metadata, it is unclear whether there is disciplinary bias within the content registered via DataCite (Robinson-Garcia et al, 2017).…”
Section: Citation-based Indicatorsmentioning
confidence: 99%
“…However, it is found that there is lack of understanding of FAIR data and principles; need for investments in the development of data tools, services, and processes to support open research; adopting FAIR principles across the broad coordinating activities and policy development at cross-disciplinary, national, and international levels [59,60]. DataCite has been steering on persistent identifiers for research data citation, discovery, and accessibility, while also emphasizing the measurement of grants and the impact that is made by funding agencies [61,62]. Hypothesis has been experimenting with open annotation use cases on preprints and discussed the burden of moderating (editorial and site), identity, and versioning among the preprint repositories [63].…”
Section: Preprints For Building Scholarly Infrastructures and Metricsmentioning
confidence: 99%
“…Most rely on the use of DOIs, which assumes that these are widely used, but this does not yet appear to be the case in archaeology: for instance, Google searches for the DOIs of random ADS archives led back to the original archive rather than to references to the archive, even in cases where the archives were known to have been reused and cited. Event services such as those being developed by DataCite and Crossref are intended to capture the broader range of reuses but are dependent on the use of persistent identifiers (Dappert et al 2017; Robinson-Garcia et al 2017). Until archaeologists consistently use DOIs or other such persistent identifiers for their data, the capture of altmetrics for archaeological data citation seems equally problematic and equally unreliable as standard data citations, as indeed is the experience elsewhere (Peters et al 2016).…”
Section: Absence Of Evidence and Evidence Of Absencementioning
confidence: 99%